PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD MUHAMMADIYAH 4 PEKANBARU - Ariyanti, Heni Ariyanti; Alim, Jesi Alexander Alim Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Issues raised in this research is to improve student learning outcomes math class III SD Muhammadiyah 4 Pekanbaru. The low learning outcomes of students because teachers still use the lecture method so that the lack of attention of students during the lessons and student think math is a difficult subject and tedious because it deals with formulas so that students feel bored. Quantum model of teaching can improve students' mathematics learning outcomes Class III SD Muhammadiyah 4 Pekanbaru. Subjects in this study were students of class III SD Muhammadiyah 4 Pekanbaru academic year 2014/2015 the number of students 38 people consisting of 26 boys and 12 girls. This research was conducted in two cycles, the first cycle was conducted in two sessions and the second cycle was also conducted two meetings and one repeat cycle end. Data collection instruments in this study was the observation sheet student, teacher observation sheet, outcomes assessment rubric and assessment process. The study is in the form of classroom action research (PTK), which aims to improve students' mathematics learning outcomes Class III SD Muhammadiyah 4 Pekanbaru in the subject matter of measurement. These results indicate that the application of the model of Quantum Teaching can improve students' mathematics learning outcomes Class III SD Muhammadiyah 4 Pekanbaru. At the beginning of the data mean the base score is 68.94, the average in the first cycle increased 8,95poin be 77.89, and the mean on the second cycle increased again 16.05 points to 93.94. On the basis of students' scores classical completeness is 44.74% of students in the first cycle classical completeness students increased 15.65 points to 60.39%. In the second cycle increased 26.45 points to 86.84%. From the results of this study concluded that the application of Quantum Teaching models can improve student learning outcomes Class III SD Muhammadiyah 4 Pekanbaru. Keywords:Model Quantum Teaching, Mathematics Learning Outcomes